Transformation of integration Indonesian islamic values on the islamic university curriculum - Amin, Nasihun; Munir, Ubaidilah; Nurjanah, Siti; Mubaidilla, Irfa'i Alfian (Al-Misbah (Jurnal Islamic Studies), 2025)
This study addresses the growing need for Islamic education grounded in local values, as globalization and the homogenization of religious thought continue to advance. Focusing on IAINU Tuban, the research examines how Islamic Nusantara values, such as harmony, tolerance, and local wisdom, have been integrated into the curriculum from 2014 to 2024 to support a moderate and contextually relevant approach to Islamic education in Indonesia. The study aims to map the historical trajectory of this integration, analyze operational challenges, and evaluate its impact on educational practices. Employing a qualitative approach with historical methods, data were collected from curriculum documents, institutional archives, stakeholder interviews, and classroom observations. The results identify three phases of integration: (1) informal adoption by lecturers (2014–2017), (2) institutionalization through special courses (2017–2020), and (3) digital-based curriculum reform (2020–2024). Although challenges such as limited teaching resources and teacher capacity remain, this integration model has contributed to strengthening a contextual Islamic identity. Future research should assess the effectiveness of digital learning and its long-term influence on student character development.